Effects of time-periodic linear coupling on two-component Bose-Einstein condensates in two dimensions - Susanto, H.; Kevrekidis, P. G.; Malomed, B. A. [UNESP]; Abdullaev, F. Kh. [UNESP] (Elsevier B.V., 2008)
We examine two-component Gross-Pitaevskii equations with nonlinear and linear couplings, assuming self-attraction in one species and self-repulsion in the other, while the nonlinear inter-species coupling is also repulsive. For initial states with the condensate placed in the self-attractive component, a sufficiently strong linear coupling switches the collapse into decay (in the free space). Setting the linear-coupling coefficient to be time-periodic (alternating between positive and negative values, with zero mean value) can make localized states quasi-stable for the parameter ranges considered herein, but they slowly decay. The 2D states can then be completely stabilized by a weak trapping potential. In the case of the high-frequency modulation of the coupling constant, averaged equations are derived, which demonstrate good agreement with numerical solutions of the full equations. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: nonlinear schrodinger equations; multiple components; linear coupling